2021
DOI: 10.3390/biology10080786
|View full text |Cite
|
Sign up to set email alerts
|

Does Coenzyme Q10 Supplementation Improve Testicular Function and Spermatogenesis in Male Mice with Chronic Kidney Disease?

Abstract: The aim of the study was to examine the potential effects of coenzyme Q10 (CoQ10) on reproductive function in a chronic kidney disease (CKD) mouse model. Nine-week-old mice were randomly assigned to two groups: sham surgery (n = 18) and CKD surgery (n = 18). After surgery, the study groups received CoQ10 (10 mg/kg body weight dissolved in corn oil by oral gavage) or corn oil as a vehicle daily for 8 weeks. The groups that underwent 5/6 nephrectomy developed significant elevations of serum BUN and creatinine le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Moreover, the CoQ10 can diminish the heat-stress-induced cellular apoptosis which is evident by Bcl2 (anti-apoptotic biomarker) up-regulation and BAX and caspase3 (apoptotic biomarkers) down-regulation (El-Khadragy et al 2020 ). Numerous studies support the outcomes of the present study under testicular stress conditions in rats such as lead acetate and lipopolysaccharide toxicity (Song et al 2017 ; El-Khadragy et al 2020 ), chronic kidney disease (Tsao et al 2021 ), and heat stress (Elokil et al 2019 ) in rabbits. Unaltered levels of FSH, LH, and E2 during the experimental time points between CoQ10 supplemented males versus control need to be interpreted cautiously taking into consideration its pulsatile secretions.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, the CoQ10 can diminish the heat-stress-induced cellular apoptosis which is evident by Bcl2 (anti-apoptotic biomarker) up-regulation and BAX and caspase3 (apoptotic biomarkers) down-regulation (El-Khadragy et al 2020 ). Numerous studies support the outcomes of the present study under testicular stress conditions in rats such as lead acetate and lipopolysaccharide toxicity (Song et al 2017 ; El-Khadragy et al 2020 ), chronic kidney disease (Tsao et al 2021 ), and heat stress (Elokil et al 2019 ) in rabbits. Unaltered levels of FSH, LH, and E2 during the experimental time points between CoQ10 supplemented males versus control need to be interpreted cautiously taking into consideration its pulsatile secretions.…”
Section: Discussionsupporting
confidence: 85%
“…Various researches maintain this proposition, demonstrating that after castration of sexually practiced males in adulthood is followed by a gradual failure in the mating behavior ( Clark, 1993 ; Davidson et al., 1978 ). In our study, Coenzyme Q10 supplementation significantly increases the percentage of birds exhibiting sexual behavior as it is one of the most commonly used antioxidants for male infertility treatment and improves erectile function ( Tsao et al., 2021 ). Moreover, the addition of CoQ10 with cadmium exhibited a considerable improvement in the percent of birds showing sexual behavior than birds exposed to cadmium only as CoQ10 protects those birds from lipid peroxidation.…”
Section: Discussionmentioning
confidence: 78%
“…Energy manufacture inside the mitochondria, which is required to sustain the sperm cell energy system and defend it against the harm of lipid peroxidation, involves coenzyme Q10 (CoQ10), as it is a part of the ubiquinone family which is known to have unique antioxidant characteristics. It is one of the furthermost extensively consumed antioxidants for male infertility treatment ( Tsao et al., 2021 ). Cd is one of the heavy metals that animals are subjected to via polluted foods and soil; Cd is reported to have many harmful effects on testicular tissue ( Zhu et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, CoQ10 may protect testosterone-producing cells from oxidative stress by scavenging ROS and inhibiting membrane lipid peroxidation [ 58 ]. A human study found that CoQ10 treatment significantly raised the FSH and LH in infertile men, suggesting that CoQ10 may be associated with hormone-regulated testosterone synthesis [ 59 ].…”
Section: Discussionmentioning
confidence: 99%